Structural changes in the demand for food in Asia - Huang, Jikun; Bouis, Howarth E. (International Food Policy Research Institute, 1996)
This paper presents an overview of changing food consumption patterns in Taiwan and China. It finds that consumption of meat quadrupled in Taiwan between the periods 1959-61 and 1989-91, while per capita rice consumption declined by one-half. In mainland China, consumption of nonstaple foods such as meat rose 10 percent. How much of these changes in diet resulted from income and price effects and how much from structural factors such as urbanization? This question has important implications for accurately forecasting the future demand for food in Asia.